An analysis of eco-labelled honey practices employed in the South African beekeeping industry : implications for agricultural sustainability - Hendricks, Lindi Leela (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.